Financial Distress, Institutional Ownership, and Earnings Management: Evidence from the Energy Sector - Widya Winata; Sri Hastuti; Sri Suryaningsum (Journal of International Conference Proceedings, 2024)
This study seeks to analyze the effect of financial distress on earnings management, focusing on institutional ownership as a potential moderating variable. Employing a quantitative research approach, this study utilizes secondary data sourced from the financial statements of energy industry sector companies listed on the Indonesia Stock Exchange (IDX) and the companies' official websites during the period 2019–2023. The purposive sampling technique was used to select a representative sample, ensuring relevance and data quality. The findings reveal that financial distress positively influences earnings management, indicating that companies experiencing financial difficulties are more likely to engage in earnings management practices, possibly as a strategic response to mitigate the appearance of financial instability. However, the study also finds that institutional ownership does not moderate the relationship between financial distress and earnings management. This suggests that the presence of institutional investors does not significantly alter or mitigate the impact of financial distress on a company's propensity to engage in earnings management. These results provide important insights for stakeholders, including regulators and investors, by highlighting the implications of financial distress on corporate reporting behavior and the limited role of institutional ownership in curbing earnings management practices